1981
DOI: 10.1152/ajpheart.1981.240.2.h209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changes in arterial O2 content on cerebral blood flow in the lamb

Abstract: The effect of variations in arterial O2 content (CaO2) on the cerebrovascular bed of seven unanesthetized newborn lambs was studied as the hematocrit and arterial PO2 (PaO2) were varied. Each subject was studied at a high hematocrit [44 +/- 3% (SD)] and a low hematocrit [24 +/- 3%]. At each hematocrit level the PaO2 was changed over a range of 30-150 mmHg. The relationship between cerebral blood flow and PO2 depended on hematocrit and vice versa. To the contrary, the relationship of blood flow to CaO2 was inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
73
0
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 0 publications
13
73
0
1
Order By: Relevance
“…Numerous previous studies have demonstrated that, after birth, CBF gradually decreases, which is considered to be an autoregulatory process in response to an increase in oxygenation (14,17,18). This response was observed in SI lambs, with CBF gradually decreasing from 40.2 Ϯ 7.8 mL/min/kg at 1 min after birth to 19.9 Ϯ 4.3 mL/min/kg by the end of the experiment.…”
Section: Discussionmentioning
confidence: 71%
“…Numerous previous studies have demonstrated that, after birth, CBF gradually decreases, which is considered to be an autoregulatory process in response to an increase in oxygenation (14,17,18). This response was observed in SI lambs, with CBF gradually decreasing from 40.2 Ϯ 7.8 mL/min/kg at 1 min after birth to 19.9 Ϯ 4.3 mL/min/kg by the end of the experiment.…”
Section: Discussionmentioning
confidence: 71%
“…Parameters compared included measured physiologic variables (oxygen contents, blood gases, microsphere whole brain, and regional blood flows) as well as calculated variables. CMR0 2 , 00, fractional extraction of oxygen, CBF per unit Oz consumption [1/(CaOz-CvOz)] were calculated as described previously (10,15).…”
Section: Resultsmentioning
confidence: 99%
“…The neonatal lamb was chosen for these studies because it is a well-established model for the evaluation of the cerebral circulation (l0, 15,26). The surgical procedures are tolerated nicely and an indwelling sagittal sinus catheter for sampling cerebral venous drainage can be reliably placed.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, interruption of placental blood flow with hypoxia and hypercarbia both independently increase CBF. [11][12][13] In addition, the vascular responses to both partial pressure of carbondioxide (PaCO 2 ) and partial pressure of oxygen (PaO 2 ) vary widely amongst brain regions. For example, cerebral white matter as compared to brainstem and cortical structures has limited vasodilatory responses to both PaCO 2 and hypoxia.…”
Section: Defining Asphyxiamentioning
confidence: 99%